Further Investigations of Nitroheterocyclic Compounds as Potential Antikinetoplastid Drug Candidates - García-Estrada, Carlos; Pérez-Pertejo, Yolanda; Domínguez-Asenjo, Bárbara; Holanda, Vanderlan Nogueira; Murugesan, Sankaranarayanan; Martínez-Valladares, María; Balaña-Fouce, Rafael; Reguera, Rosa M. (Biomolecules (Basel, Switzerland), 2023)
Due to the lack of specific vaccines, management of the trypanosomatid-caused neglected tropical diseases (sleeping sickness, Chagas disease and leishmaniasis) relies exclusively on pharmacological treatments. Current drugs against them are scarce, old and exhibit disadvantages, such as adverse effects, parenteral administration, chemical instability and high costs which are often unaffordable for endemic low-income countries. Discoveries of new pharmacological entities for the treatment of these diseases are scarce, since most of the big pharmaceutical companies find this market unattractive. In order to fill the pipeline of compounds and replace existing ones, highly translatable drug screening platforms have been developed in the last two decades. Thousands of molecules have been tested, including nitroheterocyclic compounds, such as benznidazole and nifurtimox, which had already provided potent and effective effects against Chagas disease. More recently, fexinidazole has been added as a new drug against African trypanosomiasis. Despite the success of nitroheterocycles, they had been discarded from drug discovery campaigns due to their mutagenic potential, but now they represent a promising source of inspiration for oral drugs that can replace those currently on the market. The examples provided by the trypanocidal activity of fexinidazole and the promising efficacy of the derivative DNDi-0690 against leishmaniasis seem to open a new window of opportunity for these compounds that were discovered in the 1960s. In this review, we show the current uses of nitroheterocycles and the novel derived molecules that are being synthesized against these neglected diseases.